Free Your Mind: Emotional Expressive Flexibility Moderates the Effect of Stress on Post-Traumatic Stress Disorder Symptoms - Einat Levy-Gigi (International Journal of Molecular Sciences, 2020)
Servicemen are exposed to high levels of stress as part of their daily routine, however, studies which tested the relationship between stress and clinical symptoms reached inconsistent results. The present study examines the role of expressive flexibility, which was determined according to the ability to enhance or suppress either negative or positive emotional expression in conflictual situations, as a possible moderator between stress and Post-Traumatic Stress Disorder (PTSD) symptoms. A total of 82 active-duty firefighters (all men, age range = 25–66, M = 33.59, SD = 9.56, range of years in duty service = 2–41, M = 14.37, SD = 11.79), with different duty-related repeated traumatic exposure, participated in the study. We predicted and found that firefighters with low, but not high, expressive flexibility showed a significant positive correlation between duty-related traumatic exposure and PTSD symptomology (t(81) = 3.85, p < 0.001). Hence, the greater the exposure the higher level of symptoms they exhibited. In addition, we found a difference between the moderating roles of suppressing positive and negative emotional expression, as high but not low, ability to suppress the expression of negative emotions (t(81) = 1.76, p > 0.05), as low but not high, ability to suppress the expression of positive emotions (t(81) = 1.6, p > 0.05), served as a protective factor in buffering the deleterious effect of repeated traumatic exposure. The results provide a pivotal support for the growing body of evidence that a flexible emotional profile is an adaptive one, in dealing with negative life events. However, while there is a need to update behavior, the direction of the adaptive update may differ as a function of valance.